Low Paraoxonase 1 Activity Predicts Mortality in Surgical Patients with Sepsis. (9th February 2014) - Bojic, Suzana; Kotur-Stevuljevic, Jelena; Kalezic, Nevena; Jelic-Ivanovic, Zorana; Stefanovic, Aleksandra; Palibrk, Ivan; Memon, Lidija; Kalaba, Zdravko; Stojanovic, Marina; Simic-Ogrizovic, Sanja
Abstract : Introduction . State of severe oxidative stress is encountered in sepsis. Paraoxonase 1 (PON1) protects against oxidative stress but also undergoes inactivation upon that condition. We investigated PON1 activity in surgical patients with sepsis in relation to oxidative stress status, inflammation, disease severity, and survival. Methods . Prospective observational study. Sixty-nine surgical patients with sepsis were compared to 69 age/sex matched healthy controls. PON1 paraoxonase and diazoxonase activities, selected biochemical, hematological and oxidative stress parameters were measured on admission to ICU and 24, 48, 72, and 96 hours later. Disease severity scores were calculated daily. Results . Septic patients had significantly lower PON1 activities compared to control group at all time points. PON1 activities had good capacity to differentiate septic patients from healthy controls. Low PON1 activities were associated with higher disease severity scores and higher risk of death. Correlation between PON1 activity and markers of inflammation failed to reach significance. Decrease in PON1 activity was correlated with an increase in reducing components in plasma. Conclusion . Our study demonstrated lower PON1 activity in surgical patients with sepsis compared to healthy controls. PON1 activity also reflected severity of the disease. Low PON1 activity was associated with higher mortality of surgical patients with sepsis.